Pelatihan Personal Branding Content Creator Di Media Sosial Bagi Siswa SMK Prima Unggul Kota Tangerang - Sakaril, Gufroni (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Personal Branding is a way to market that is really needed, especially in the current era of digital society. Through Personal Branding, someone can highlight the advantages and uniqueness of each media user. Considering the importance of personal branding and understanding social media, this need is implemented in Community Service activities with the theme Personal Branding Content Creator on Social Media for Students of Prima Unggul Vocational School, Tangerang City. A content creator needs to consider engagement, awareness, personnal branding so that the storyline you want to convey can attract attention. Understanding social media as a medium is very important for portfolios to find out students' talents as a means to find job vacancies or open an independent business after they graduate from school. This is in accordance with the vision of Prima Unggul Vocational School, Tangerang City, including increasing the competency of students who are ready to enter the world of work in the national and global markets. Increasing the competence of students who are able to keep up with the latest technological developments. In this community service, apart from introducing the importance of personal branding, they also explain the characteristics of social media which are the basis for building awareness and engagement on the accounts they manage. Training on how to manage social media to build personal branding is useful for students. Digital traces will not be lost, so students' social media accounts must contain positive and useful content for themselves and their followers.